Method For Manufacturing Damage-Healable Resettable Alloys Through Multi-Step Resetting Process And Resettable Alloys Manufactured Thereby
Patent Information
- Application Number
- KR1020250030617
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2026-09-17
Smart Images

Figure PAT00003_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing a characteristic recovery alloy, a characteristic recovery alloy manufactured therefrom, and a method for restoring the characteristics of a characteristic recovery alloy that has undergone deformation. Background Technology
[0002] With the rapid advancement of science and technology, modes of transportation are becoming faster and structures are becoming larger, thereby increasing the risk associated with accidents. Consequently, there is growing interest in ensuring safety by extending the lifespan of materials. In this regard, self-healing and stress-relieving heat treatment are being researched as representative mechanisms for extending material lifespan.
[0003] The self-healing mechanism operates when a substance capable of closing a crack within the material spontaneously diffuses into the defect region as the crack propagates due to stress. However, metals have very low diffusion coefficients at room temperature, making it difficult for the self-healing mechanism to function. Meanwhile, stress relaxation heat treatment is a mechanism that extends material life by applying external energy to relieve residual stress. However, when performing stress relaxation heat treatment, phenomena such as grain growth and defect disappearance occur simultaneously with the relief of residual stress, which has the limitation of causing a rapid decrease in material strength.
[0004] Patent Document 1 discloses a characteristic recovery alloy and a manufacturing process thereof that introduces a characteristic recovery mechanism. Specifically, the characteristic recovery mechanism involves applying external energy to a material subjected to deformation to reset it to the phase and microstructure prior to deformation. While stress relaxation heat treatment is merely intended to relieve residual stress, the characteristic recovery mechanism differs in that it restores the initial microstructure prior to deformation by highly controlling the microstructure so that quasi-static reversible phase change behavior is exhibited in regions where specific elements are segregated.
[0005] However, the characteristic recovery alloy manufacturing process and the heat treatment (R-treatment) required to recover the austenite phase during the recovery treatment process of Patent Document 1 are high in terms of time cost, and the characteristic recovery alloy has limitations in that mechanical properties gradually deteriorate as microstructural defects such as dislocations accumulate as use and recovery treatment are repeated, and the present invention aims to overcome these limitations. Prior art literature
[0006] (Patent Document 0001) KR 10-2405855 B1 The problem to be solved
[0007] The technical problem that the present invention aims to solve is to provide a method for manufacturing a characteristic recovery alloy with improved characteristic recovery ability.
[0008] However, the problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned problems will be clearly understood by those skilled in the art from the description below. means of solving the problem
[0009] One embodiment of the present invention provides a method for manufacturing a characteristic recovery alloy comprising a BCT-FCC microstructure capable of metastable reversible phase transformation, wherein the manufacturing method comprises sequentially performing the following steps.
[0010] (a) Fe 100-a-b-c-d Mn a Cr b W c C d (3≤a≤15, 0 <b≤11.87, 0<c≤3 및 0<d≤2.01 wt%)의 조성을 갖도록 합금 원소를 용해하여 합금화하는 단계;
[0011] (b) a step of heat-treating the alloy and then rapidly cooling it to form a homogenized body-centered tetragonal (BCT) martensite phase;
[0012] (c) Minimum temperature (T) depending on the Mn composition of the above alloy 1,min (℃) = -18 × wt%(Mn) + 640) or higher, maximum temperature (T 1,max A step of heat-treating the alloy at (°C) = -18 × wt%(Mn) + 820) or lower, followed by rapid cooling to form Mn segregation and face-centered cubic (FCC) austenite precipitates;
[0013] (d) Minimum temperature (T) depending on the Mn composition of the above alloy 2,min (℃) = -18 × wt%(Mn) + 820) or higher, maximum temperature (T 2,max (℃) = 0.8 × T m A step of heat-treating the alloy below and then rapidly cooling it to remove the FCC austenite precipitate phase and form a homogenized BCT martensite phase; and
[0014] (e) Minimum temperature (T) depending on the Mn composition of the above alloy 1,min (℃) = -18 × wt%(Mn) + 640) or higher, maximum temperature (T 1,max A step of re-forming an FCC austenite precipitate phase by heat-treating the alloy at (℃) = -18 × wt%(Mn) + 820) or less, followed by rapid cooling.
[0015] Another embodiment of the present invention provides a characteristic recovery alloy comprising a BCT-FCC microstructure capable of metastable reversible phase transition, manufactured by the manufacturing method according to the present invention.
[0016] Another embodiment of the present invention provides a method for restoring the properties of a property-restoring alloy that has undergone deformation due to use and is manufactured by the manufacturing method according to the present invention, wherein the following steps are performed sequentially.
[0017] (A) A characteristic recovery alloy that has been deformed by use, at a minimum temperature (T) according to the Mn composition of the alloy. 2,min (℃) = -18 × wt%(Mn) + 820) or higher, maximum temperature (T 2,max (℃) = 0.8 × T m A step of rapid cooling after heat treatment below ); and
[0018] (B) Lowest temperature (T) depending on the Mn composition of the above alloy 1,min (℃) = -18 × wt%(Mn) + 640) or higher, maximum temperature (T 1,max A step of heat-treating the alloy at (℃) = -18 × wt%(Mn) + 820) or less, followed by rapid cooling. Effects of the invention
[0019] A method for manufacturing a characteristic recovery alloy according to one embodiment of the present invention can provide a characteristic recovery alloy with improved characteristic recovery ability by preventing the accumulation of microstructural defects such as dislocations.
[0020] A method for manufacturing a characteristic recovery alloy according to one embodiment of the present invention can shorten the heat treatment time for precipitating the austenite phase.
[0021] The effects of the present invention are not limited to those described above, and unmentioned effects will be clearly understood by those skilled in the art from the present specification and the accompanying drawings. Brief explanation of the drawing
[0022] Figure 1 is Fe 89.48-x Mn x Cr9W 1.4 C 0.12This is the result of calculating the phase diagram according to the weight% of Mn in an alloy system having the composition using TCFE 8, an iron-based database of Thermo-Calc thermodynamic simulations. FIG. 2 is a schematic diagram of a method for manufacturing a characteristic recovery alloy according to Example 1 of the present invention. Figure 3 shows backscattered electron diffraction (EBSD) results showing the microstructure of the alloy performed up to step (d) of the manufacturing method of Example 1 and the microstructure of the alloy performed up to step (e) of (b). Figure 4 shows a TEM image of the alloy prepared up to step (d) of the manufacturing method of Example 1, and the weight% of Mn and Fe in the area indicated in the TEM image. Figure 5 schematically illustrates the change in the microstructure and Mn concentration of an alloy according to the alloy characteristic recovery method according to one embodiment of the present invention. Figure 6 shows EBSD results indicating the microstructure of the alloy subjected to the return method of Example 2. Figure 7 shows a TEM image of the alloy subjected to the return method of Example 2, and the weight% of Mn and Fe in the area indicated in the TEM image. Figure 8 shows a stress-strain graph of the characteristic return alloy measured according to a repetitive strain-return cycle in Example 3. Figure 9 shows a stress-strain graph of the characteristic return alloy measured according to a repetitive strain-return cycle in Example 3. Specific details for implementing the invention
[0023] Throughout this specification, when a part is described as "comprising" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.
[0024] Throughout this specification, when a component is described as being located "on" another component, this includes not only cases where a component is in contact with another component, but also cases where another component exists between the two components.
[0025] Throughout this specification, the “T” of the alloy m " represents the melting temperature of the alloy.
[0026] Throughout the entire specification, the unit "parts by weight" may refer to the ratio of weight between each component.
[0027] Throughout this specification, "A and / or B" means "A and B, or A or B".
[0028] One embodiment of the present invention provides a method for manufacturing a characteristic recovery alloy comprising a BCT-FCC microstructure capable of metastable reversible phase transformation, wherein the manufacturing method comprises sequentially performing the following steps.
[0029] (a) Fe 100-a-b-c-d Mn a Cr b W c C d (3≤a≤12, 0 <b≤11.87, 0<c≤3 및 0<d≤2.01 wt%)의 조성을 갖도록 합금 원소를 용해하여 합금화하는 단계;
[0030] (b) a step of heat-treating the alloy and then rapidly cooling it to form a homogenized body-centered tetragonal (BCT) martensite phase;
[0031] (c) Minimum temperature (T) depending on the Mn composition of the above alloy 1,min (℃) = -18 × wt%(Mn) + 640) or higher, maximum temperature (T 1,max A step of heat-treating the alloy at (°C) = -18 × wt%(Mn) + 820) or lower, followed by rapid cooling to form Mn segregation and face-centered cubic (FCC) austenite precipitates;
[0032] (d) Minimum temperature (T) depending on the Mn composition of the above alloy 2,min (℃) = -18 × wt%(Mn) + 820) or higher, maximum temperature (T 2,max (℃) = 0.8 × T m A step of heat-treating the alloy below and then rapidly cooling it to remove the FCC austenite precipitate phase and form a homogenized BCT martensite phase; and
[0033] (e) Minimum temperature (T) depending on the Mn composition of the above alloy 1,min (℃) = -18 × wt%(Mn) + 640) or higher, maximum temperature (T 1,max A step of re-forming an FCC austenite precipitate phase by heat-treating the alloy at (℃) = -18 × wt%(Mn) + 820) or less, followed by rapid cooling.
[0034] Another embodiment of the present invention provides a characteristic recovery alloy comprising a BCT-FCC microstructure capable of metastable reversible phase transition, manufactured by the manufacturing method according to the present invention.
[0035] According to one embodiment of the present invention, the BCT-FCC microstructure may comprise a BCT martensite phase matrix; and an FCC austenite precipitate phase present within the matrix.
[0036] Specifically, the volume fraction of the FCC austenite precipitate phase in the BCT-FCC microstructure may be 1% to 50%, 1% to 30%, 1% to 25%, 5% to 50%, 5% to 30%, 5% to 25%, 10% to 50%, 10% to 30%, or 10% to 25%.
[0037] According to one embodiment of the present invention, the FCC austenite precipitate phase may be formed at the lath boundary of the acicular martensite.
[0038] According to one embodiment of the present invention, it is preferable that the FCC austenite precipitate has a size of 10 μm or less.
[0039] The above FCC precipitate phase transforms into a martensite phase through stress-induced transformation during the use or deformation of the characteristic return alloy.
[0040] The characteristic recovery alloy of the present invention can recover mechanical properties and microstructure by recovering an alloy containing a stress-induced transformed martensite phase in the following manner and selectively reverse transforming only the portion of the stress-induced transformed martensite phase back into an austenite phase.
[0041] A characteristic recovery alloy according to one embodiment of the present invention may have excellent mechanical properties such as yield strength, ultimate tensile strength (UTS), and elongation.
[0042] Specifically, the yield strength of the above characteristic recovery alloy may be 700 MPa or more, 700 to 1200 MPa, 700 to 1100 MPa, 700 to 1000 MPa, 800 to 1200 MPa, 800 to 1100 MPa, or 800 to 1000 MPa.
[0043] The ultimate tensile strength of the above characteristic recovery alloy may be 950 MPa or more, 950 MPa to 1300 MPa, 1000 MPa to 1300 MPa, 950 MPa to 1200 MPa, or 1000 MPa to 1200 MPa.
[0044] The maximum elongation of the above characteristic recovery alloy may be 10% or more, 15% or more, 20% or more, 25% or more, or 30% or more, and the upper limit value is not specifically limited.
[0045] According to one embodiment of the present invention, the yield strength of the characteristic recovery alloy that has undergone one or more strain-recovery cycles exhibits a difference of 10% or less compared to the yield strength of the characteristic recovery alloy immediately after manufacturing, and the strain-recovery cycle involves deforming the alloy by a tensile strain of up to 90% of the UTS strain, then heat-treating the deformed alloy at 850°C or higher and 1200°C or lower for 30 seconds or more and 30 minutes or less, followed by rapid cooling, and the lowest temperature (T) according to the Mn composition of the cooled alloy 1,min (℃) = -18 × wt%(Mn) + 640) or higher, maximum temperature (T 1,max (°C) = -18 × wt%(Mn) + 820) Heat treatment at a temperature of 1 minute or more and 100 minutes or less may be performed as one cycle.
[0046] Specifically, another embodiment of the present invention provides a method for restoring the properties of a property-restoring alloy that has undergone deformation due to use and is manufactured by the manufacturing method according to the present invention, by sequentially performing the following steps.
[0047] (A) A characteristic recovery alloy that has been deformed by use, at a minimum temperature (T) according to the Mn composition of the alloy. 2,min (℃) = -18 × wt%(Mn) + 820) or higher, maximum temperature (T 2,max (℃) = 0.8 × T m A step of heat treating and quenching below ); and
[0048] (B) Lowest temperature (T) depending on the Mn composition of the above alloy 1,min (℃) = -18 × wt%(Mn) + 640) or higher, maximum temperature (T 1,maxA step of heat-treating the alloy and rapidly cooling it at (℃) = -18 × wt%(Mn) + 820) or less.
[0049] According to one embodiment of the present invention, the heat treatment of step (A) may be performed for 30 seconds or more and 30 minutes or less, and the heat treatment of step (B) may be performed for 1 minute or more and 100 minutes or less.
[0050] Hereinafter, each step of the method for manufacturing a characteristic recovery alloy according to one embodiment of the present invention will be explained in more detail.
[0051] (a) Fe 100-a-b-c-d Mn a Cr b W c C d (3≤a≤15, 0 <b≤11.87, 0<c≤3 및 0<d≤2.01 wt%)의 조성을 갖도록 합금 원소를 용해하여 합금화하는 단계
[0052] Mn is an element for the expression of segregation behavior and stress-induced transformation, and the heat treatment temperature range in steps (c) to (e) described below is determined according to the content of Mn.
[0053] Cr is an element that readily dissolves in iron and forms a dense oxide structure at high temperatures, which can contribute significantly to increasing oxidation resistance. Additionally, Cr lowers the stacking fault energy within FCC alloys, so even if added in large quantities, it can prevent interference with the development of stress-induced transformation. Meanwhile, since the maximum solubility of Cr in the austenite phase is 11.87 wt% during alloy homogenization and heat treatment into an austenite single phase, the composition range was limited accordingly.
[0054] Although W can be advantageous for strengthening the strength, oxidation resistance, and corrosion resistance of the alloy at high temperatures, if alloyed with a content of more than 3 wt%, it can easily form carbides by reacting with carbon present in the alloy, so the composition range was limited accordingly.
[0055] It is known that since C is dissolved in Fe and stabilizes the body-centered cubic (BCC) crystal structure at low temperatures, it easily forms an α' martensite phase with a BCT structure when cooled from high to low temperatures. Additionally, C can be located at interstitial sites and promote martensite transformation. Meanwhile, since C also has a maximum solubility of 2.01 wt% in the austenite phase, the composition range was limited accordingly.
[0056] In addition, to improve the strength of the alloy, one or more selected from the group consisting of V, Nb, Mo, and Ta may be added to the above composition up to 5 wt% of the total weight. In the above composition, Fe occupies the remaining weight as a base element, excluding the weight occupied by Mn, Cr, W, C, and one or more of the elements among V, Nb, Mo, and Ta.
[0057] According to one embodiment of the present invention, step (a) may involve melting together a material having a purity of 99.9% or higher, preferably 99.99% or higher, and then rapidly cooling it. However, the material is not specifically limited to a purity range of 99.9% or higher. Preferably, step (a) may be performed by an arc-melting method capable of rapidly forming a homogeneous solid solution in bulk form.
[0058] According to one embodiment of the present invention, the alloying in step (a) may utilize induction casting, which allows for the production of a homogeneous alloy by melting the parent element using an electric field, in addition to arc melting. Alternatively, it is also possible to manufacture the alloy through a commercial casting process by utilizing resistance heating, which enables precise temperature control. Furthermore, in addition to commercial casting methods capable of melting raw metals, the alloy may also be manufactured by preparing the raw material into a powder and sintering it at high temperature and high pressure using spark plasma sintering or hot isostatic pressing via powder metallurgy. Using such sintering methods offers the advantage of facilitating more precise microstructural control and the manufacture of parts of desired shapes.
[0059] (b) a step of heat-treating the alloy and then rapidly cooling it to form a homogenized body-centered tetragonal (BCT) martensite phase.
[0060] The heat treatment in step (b) is a step for homogenizing the master alloy alloyed in step (a).
[0061] According to one embodiment of the present invention, the heat treatment of step (b) may be performed at a temperature of 850°C or higher and 1230°C or lower for 0.5 hours or longer and 96 hours or less. Since the same state is maintained after a certain time, there is no meaning in limiting the maximum time for the homogenization time for a specimen that has been homogenized. However, if the homogenization heat treatment is performed for more than 96 hours, deterioration occurs through the precipitation of unexpected additional phases, which is undesirable.
[0062] Specifically, Fe 100-a-b-c-d Mn a Cr b W c C d(3≤a≤12, 0 <b≤11.87, 0<c≤3 및 0<d≤2.01 wt%)의 조성을 갖는 합금은 850 ℃ 이상의 온도에서 완전한 FCC 오스테나이트 상을 가질 수 있다. 따라서, (b)단계의 열처리 및 급냉을 수행함으로써 균질화된 BCT 마르텐사이트 상을 형성할 수 있다.
[0063] According to one embodiment of the present invention, the alloy that has undergone step (b) may be a single BCT phase, or the volume fraction of the FCC phase may be less than 5%, 3%, 2%, or 1%.
[0064] According to one embodiment of the present invention, the rapid cooling of step (b) may be performed at a cooling rate of 10 K / sec or higher. By satisfying the above cooling rate, additional transformations in which the alloy transitions to another phase including pearlite during the cooling process after heat treatment may not occur. For example, the rapid cooling may be performed by water cooling. The rapid cooling of steps (c) to (e) described below may be performed under the above conditions.
[0065] (c) Minimum temperature (T) depending on the Mn composition of the above alloy 1,min (℃) = -18 × wt%(Mn) + 640) or higher, maximum temperature (T 1,max A step of heat-treating the alloy at a temperature (°C) = -18 × wt%(Mn) + 820) or lower, followed by rapid cooling to form Mn segregation and face-centered cubic (FCC) austenite precipitates.
[0066] The heat treatment in step (c) is a step for forming Mn segregation and face-centered cubic (FCC) austenite precipitates.
[0067] Specifically, Fe 100-a-b-c-d Mn a Cr b W c C d (3≤a≤15, 0 <b≤11.87, 0<c≤3 및 0<d≤2.01 wt%)의 조성을 갖는 합금 시스템에서 Mn 조성에 따라 최저 온도(T 2,min (℃) = -18 × wt%(Mn) + 820) or higher, maximum temperature (T 2,max (℃) = 0.8 × T mThe temperature below is a region where the BCT phase and the FCC phase coexist, and heat treatment in the above temperature range may be suitable for forming Mn segregation and FCC austenite precipitates.
[0068] According to one embodiment of the present invention, the heat treatment of step (c) may be performed for 0.1 hours or more and 192 hours or less.
[0069] (d) Minimum temperature (T) depending on the Mn composition of the above alloy 2,min (℃) = -18 × wt%(Mn) + 820) or higher, maximum temperature (T 2,max (℃) = 0.8 × T m A step of heat-treating the alloy below and then rapidly cooling it to remove the FCC austenite precipitate phase and form a homogenized BCT martensite phase.
[0070] The heat treatment in step (d) is a step for transforming the FCC austenite precipitate formed in step (c) into a BCT phase and forming a homogenized BCT martensite phase.
[0071] According to one embodiment of the present invention, the alloy that has undergone step (d) may be a single BCT phase, or the volume fraction of the FCC phase may be less than 5%, 3%, 2%, or 1%.
[0072] According to one embodiment of the present invention, the heat treatment of step (d) may be performed for 30 seconds or more and 30 minutes or less.
[0073] According to one embodiment of the present invention, the maximum temperature (T) of the (d) step heat treatment 2,max (℃) = 0.8 × T m ) is the alloy melting temperature (T m It may be a temperature equivalent to 0.8 times ). Or, the maximum temperature of the heat treatment in step (d) may be 1230 ℃, which is 0.8 times the melting point of iron, the main alloying element, 1538 ℃.
[0074] (d) As the heat treatment of step (d) satisfies the above temperature and time range, the diffusion length may be smaller than the size of the lath boundary of the martensite phase and the austenite precipitate phase.
[0075] Specifically, in the heat treatment of step (d), the diffusion distance may be 500 nm or less, 400 nm or less, 300 nm or less, 200 nm or less, and more preferably 100 nm or less.
[0076] (d) By satisfying the condition that the diffusion distance resulting from the heat treatment in step (d) is smaller than the size of the acicular interface of the martensite phase and the austenite precipitate phase, the entire microstructure is transformed into the FCC phase without eliminating the Mn segregation formed in step (c), and then when rapidly cooled, a homogenized BCT phase can be formed.
[0077] (e) Minimum temperature (T) depending on the Mn composition of the above alloy 1,min (℃) = -18 × wt%(Mn) + 640) or higher, maximum temperature (T 1,max A step of re-forming an FCC austenite precipitate phase by heat-treating the alloy at (℃) = -18 × wt%(Mn) + 820) or less, followed by rapid cooling.
[0078] The heat treatment in step (e) is a step that reforms the FCC precipitate removed in step (d) to complete the BCT-FCC microstructure.
[0079] According to one embodiment of the present invention, the heat treatment of step (e) may be performed for 1 minute or more and 100 minutes or less. Specifically, the heat treatment of step (e) is sufficient with a heat treatment of 10 minutes at 550°C, which is due to the formation of an FCC precipitate phase at the Mn segregation site being induced during the short heat treatment by maintaining the segregation in step (d).
[0080] Hereinafter, the present invention will be described in detail with reference to examples to specifically explain the invention. However, the embodiments according to the present invention may be modified in various different forms, and the scope of the present invention is not to be interpreted as being limited to the embodiments described below. The embodiments of this specification are provided to more completely explain the present invention to those with average knowledge in the art.
[0081] Unless otherwise noted, the thermodynamic simulation results of the present invention were all calculated using the same database and software.
[0082] Figure 1 is Fe 89.48-x Mn x Cr9W 1.4 C 0.12 The phase diagram according to the weight% of Mn in an alloy system having the composition is the result of calculating it using TCFE 8, an iron-based database of Thermo-Calc thermodynamic simulation. As shown in Figure 1, the region where the BCC and FCC phases coexist is within the area indicated by the red dashed line. In addition, in the region where the weight% of Mn is 3 to 12, the temperature of the upper red dashed line was calculated to satisfy the equation -18×wt%(Mn) + 820 ℃, and the temperature of the lower red dashed line was calculated to satisfy the equation -18×wt%(Mn) + 640 ℃. That is, by heat-treating an alloy having a single BCT martensite phase at a temperature between (-18×wt%(Mn) + 640) ℃ and (-18×wt%(Mn) + 820) ℃ and then rapidly cooling, an FCC austenite precipitate phase can be formed within the BCT martensite matrix, thereby forming a BCT-FCC microstructure capable of metastable reversible phase transformation. The reason it is labeled as BCC in Figure 1 is that a thermodynamic database for the BCT martensite phase has not been established in the CALPHAD methodology, and because the difference in free energy between the two phases is small, the BCC phase is generally used to represent the BCT martensite phase when plotting the phase diagram.
[0083] Evaluation of mechanical properties according to Mn weight%
[0084] Fe 89.48-x Mn x Cr9W 1.4 C 0.12Alloys were prepared by controlling the Mn content as shown in Table 1 below. At this time, the alloys according to all embodiments of the present invention were prepared using an arc-melting method capable of rapidly forming a homogeneous solid solution in bulk form, with parent elements having a purity of 99.99% or higher. The prepared alloys were heat-treated at 980°C for 1 hour and rapidly cooled to prepare homogenized alloys, and the yield stress (YS), ultimate tensile stress (UTS), and elongation were measured and are shown in Table 1.
[0085] Mn content x Strength (MPa) Elongation YS UTS ε (%) 4 687 996 15.4 5 736 1043 16.6 6 713 997 14.9 7 768 1116 11 8 718 1044 13.9 9 814 1064 14.1 10 643 1137 16.2 11 521 1232 18.1 12 315 1210 12.1 15 218 975 29.7
[0086] To utilize the segregation phenomenon of Mn, a higher Mn content is advantageous. This is because, even under the same heat treatment, Mn segregates at higher concentrations at grain boundaries, which can induce localized phase transformations. Therefore, it is recommended to alloy with as high a concentration of Mn as possible. Meanwhile, for the developed alloy to be practically utilized as a structural material capable of restoring its properties, possessing a high yield stress is also critical. A material with a higher yield stress means that less damage accumulates within the material when the same stress is applied, which is a favorable condition for property restoration. As shown in Table 1, yield strength increased as the Mn content gradually increased, and Fe with 9 wt% Mn 80.48 Mn9Cr9W 1.4 C 0.12 The yield strength was best in the composition. However, it was confirmed that the yield strength decreased again when the Mn content exceeded 9 wt%.
[0087] Example 1. Preparation of a property-recovery alloy
[0088] Fe 80.48 Mn9Cr9W 1.4 C 0.12 A master alloy having the composition of was prepared.
[0089] FIG. 2 is a schematic diagram of a method for manufacturing a characteristic recovery alloy according to Example 1 of the present invention.
[0090] As shown in FIG. 2, the method for manufacturing a characteristic recovery alloy of the present invention comprises: (b) (Homogenization) heat-treating the alloy at 980 °C for 1 hour and quenching it to form a homogenized single body-centered tetragonal (BCT) martensite phase; and (c) (Reversion 1) heat-treating the alloy at 550 °C for 20 hours in a region where the BCC phase and FCC phase coexist, and quenching it to form Mn segregation and FCC austenite precipitates. The FCC precipitates may be formed at the lath boundary of the acicular martensite.
[0091] Then, (d) the (austenitizing) alloy is heat-treated at 980 °C for 1 minute to convert it entirely into the FCC phase, and then quenched to form a single body-centered tetragonal (BCT) martensite phase. At this time, by heat-treating for 1 minute at 980 °C, a temperature at which only the FCC phase exists, the BCT-FCC microstructure formed in step (c) is entirely converted into the FCC phase, and simultaneously, any remaining structural defects can be completely eliminated. Additionally, since a heat treatment of 1 minute is too short a time for Mn elements to diffuse, Mn segregation may be maintained. Therefore, the microstructure of the alloy obtained by quenching in step (d) has a single BCT martensite phase, but Mn segregation exists at the acicular martensite interface.
[0092] Finally, (e) (Reversion 2) alloy is heat-treated again at 550°C for 10 minutes and then rapidly cooled, thereby reforming an FCC precipitate phase at the location of Mn segregation, and producing the characteristic recovery alloy of the present invention.
[0093] After each of the above steps, the microstructure is ((a) step, (b) step) BCT martensite, ((c) step) BCT martensite + FCC austenite, ((d) step) BCT martensite, and ((e) step) BCT martensite + FCC austenite.
[0094] To explain this in more detail, EBSD phase maps were captured for the microstructure of the alloy processed up to step (d) of Example 1 and the alloy processed up to step (e), and are shown in FIG. 3 (a) and (b), respectively. As shown in FIG. 3 (a), the alloy heat-treated at 980 °C for 1 minute and then rapidly cooled exists almost entirely in the BCT martensite phase, and the fraction of the FCC phase (f γ ) was limited to approximately 0.6%. As shown in Fig. 3(b), it can be confirmed that the alloy heat-treated at 550 °C for 10 minutes and then quenched following step (d) has a well-formed BCT-FCC microstructure in which an FCC phase is formed within the BCT matrix, and the fraction of the FCC phase (f γ ) was about 17%.
[0095] Furthermore, transmission electron microscopy (TEM) analysis was performed to observe Mn segregation in the alloy obtained during the manufacturing process of Example 1 above.
[0096] Figure 4 shows TEM images of two parts of the alloy that were processed up to step (d) of Example 1, and the weight percentages of Mn and Fe in the areas indicated in the TEM images.
[0097] As shown in Fig. 4, it can be confirmed that although the BCT phase was formed in all of the alloys obtained by heat treatment at 980°C for 1 minute (d) and then rapid cooling, the Mn segregation formed in step (c) did not disappear and remained present, and this phenomenon could be observed uniformly across the entire area of the specimen.
[0098] Example 2. property restoration treatment of deformed property restoration alloys
[0099] Using a tensile testing machine, the alloy specimen prepared in Example 1 was subjected to a tensile strain of 6%, and then (A) the deformed alloy was heat-treated at 980°C for 1 minute and then rapidly cooled, and (B) the alloy was heat-treated again at 550°C for 10 minutes and then rapidly cooled, thereby returning to its initial mechanical properties and microstructure.
[0100] Figure 5 schematically illustrates the change in the microstructure and Mn concentration of an alloy according to the alloy characteristic recovery method according to one embodiment of the present invention.
[0101] As shown in Fig. 5, the characteristic recovery alloy immediately after manufacturing has a BCT-FCC microstructure in which an FCC phase is formed within the BCT matrix, and the deformed alloy contains structural defects such as dislocations along with transformation-induced plasticity (TRIP), in which the FCC austenite phase transforms into a martensite phase. By heat-treating the deformed alloy at 980 °C for 1 minute, the BCT-FCC microstructure is entirely converted to the FCC phase, and at the same time, remaining structural defects are eliminated and the composition and microstructure are homogenized. Additionally, since a heat treatment of 1 minute is too short a time for Mn elements to diffuse, Mn segregation may be maintained. Therefore, the alloy formed entirely in the martensite phase after heat-treating at 980 °C for 1 minute and then quenching is further heat-treated at 550 °C for 10 minutes and then quenched to form an FCC phase at the Mn segregation sites.
[0102] Figure 6 shows EBSD images of (a) the characteristic return alloy prepared in Example 1, (b) the alloy subjected to tensile strain of 6%, (c) the alloy quenched after heat treatment at 980 °C for 1 minute, and (d) the alloy quenched after heat treatment at 550 °C for 10 minutes. Figure 6 illustrates the phase transition according to the process described in Figure 5 through an EBSD phase map. Specifically, the microstructure (a) of the prepared alloy changes into the microstructure (b) as the austenite phase transforms into the martensite phase due to deformation. Subsequently, through the microstructure (c) obtained after heat treatment at 980 °C for 1 minute, and further heat treatment at 550 °C for 10 minutes, it differentiates into a microstructure (d) identical to the initially prepared microstructure.
[0103] Figure 7 shows TEM images of two parts of the alloy that underwent the characteristic recovery treatment of Example 2, and the weight% of Mn and Fe in the area indicated in the TEM images.
[0104] As shown in Fig. 7, it can be confirmed that Mn segregation is clearly maintained in the alloy after applying a tensile strain of 6%, heat-treating the alloy at 980°C for 1 minute and then rapidly cooling it, and then heat-treating it again at 550°C for 10 minutes and then rapidly cooling it.
[0105] Example 3. Evaluation of mechanical properties due to repetitive deformation-return
[0106] Experiments were conducted to confirm whether the characteristic recovery alloy prepared in Example 1 has excellent shape recovery ability, in which mechanical properties are maintained without deterioration even after repeated deformation-recovery treatment.
[0107] Specifically, after applying a tensile strain of 6% to an alloy specimen using a tensile testing machine, (A) the deformed alloy was heat-treated at 980°C for 1 minute and then rapidly cooled, and (B) the deformed alloy was heat-treated again at 550°C for 10 minutes and then rapidly cooled. This process was repeated 10 times continuously for the alloy specimen prepared in Example 1 as one deformation-reset cycle.
[0108] In addition, while applying tensile deformation during the process, the yield strength and strength characteristics at 6% strain of each alloy specimen were measured. The measurement results are shown in Table 2, Figure 8, and Figure 9. In Figure 8, H&Q corresponds to the alloy specimen quenched after homogenization heat treatment during the manufacturing process of Example 1, and Pre-strain corresponds to the stress-strain curve for the experiment in which the characteristic recovery alloy, manufactured immediately after Example 1, was deformed up to 6% to test the characteristic recovery performance. Subsequently, the stress-strain curve results obtained by repeatedly performing the 6% strain and characteristic recovery processes are shown in Figure 8. Figure 9 shows the results obtained through the experiment plotted with parallel translation to verify how well characteristic recovery occurred. It was confirmed that characteristic recovery operated excellently through the fact that the overall characteristics overlapped even after repeated resets. To analyze this in more detail, the mechanical properties per cycle are shown in Table 2.
[0109] Number of return cycles Strength (MPa) YS Stress at 6% strain 0 (Example 1) 730 1078 1 750 1118 2 735 1122 3 726 1100 4 747 1123 5 754 1122 6 726 1113 7 740 1125 8 725 1133 9 727 1082 10 630 991
[0110] Using the initial properties of the alloy after manufacturing—a yield strength of 730 MPa and a stress value at 6% strain of 1078 MPa—Table 2 can be used to calculate the percentage change in properties measured in each of the 10 resetting cycles. Consequently, excluding the 10th cycle where effective recovery of properties did not occur, the analysis shows that the change in yield strength is within a maximum of 3%, and the strength value at 6% strain changes within 4%. This implies that mechanical properties recover smoothly during repeated deformation and recovery of properties.
[0111] Although the present invention has been described above by limited embodiments, the present invention is not limited thereto, and it is obvious that various modifications and variations are possible within the scope of the technical spirit of the present invention and the equivalent scope of the claims described below by those skilled in the art to which the present invention belongs.
Claims
Claim 1 A method for manufacturing a characteristic recovery alloy comprising a BCT-FCC microstructure capable of metastable reversible phase transformation, comprising the following steps sequentially: (a) Fe 100-a-b-c-d Mn a Cr b W c C d (3≤a≤15, 0 <b≤11.87, 0<c≤3 및 0<d≤2.01 wt%)의 조성을 갖도록 합금 원소를 용해하여 합금화하는 단계;(b) 합금을 열처리한 후 급냉하여 균질화된 체심정방(BCT) 마르텐사이트 상을 형성하는 단계;(c) 상기 합금의 Mn 조성에 따라 최저 온도(T 1,min (℃) = -18 × wt%(Mn) + 640) or higher, maximum temperature (T 1,max (°C) = -18 × wt%(Mn) + 820) or lower, followed by rapid cooling to form Mn segregation and face-centered cubic (FCC) austenite precipitates; (d) a minimum temperature (T) according to the Mn composition of the alloy. 2,min (℃) = -18 × wt%(Mn) + 820) or higher, maximum temperature (T 2,max (℃) = 0.8 × T m A step of heat-treating the alloy below ) and then rapidly cooling to remove the FCC austenite precipitate phase and form a homogenized BCT martensite phase; and (e) a minimum temperature (T) according to the Mn composition of the alloy 1,min (℃) = -18 × wt%(Mn) + 640) or higher, maximum temperature (T 1,max A step of re-forming an FCC austenite precipitate phase by heat-treating the alloy at (℃) = -18 × wt%(Mn) + 820) or less, followed by rapid cooling. Claim 2 A method of manufacturing according to claim 1, wherein the BCT-FCC microstructure comprises a BCT martensite phase matrix; and an FCC austenite precipitate phase of 50 volume% or less present in the matrix. Claim 3 A manufacturing method according to claim 2, wherein the FCC austenite precipitate is formed at the lath boundary of the acicular martensite. Claim 4 A manufacturing method according to claim 1, wherein the heat treatment of step (b) is performed at a temperature of 850°C or higher and 1230°C or lower for 0.5 hours or more and 96 hours or less. Claim 5 A manufacturing method according to claim 1, wherein the heat treatment of step (c) is performed for 0.1 hours or more and 192 hours or less. Claim 6 A manufacturing method according to claim 1, wherein the heat treatment of step (d) is performed for 30 seconds or more and 30 minutes or less. Claim 7 A manufacturing method according to claim 1, wherein the heat treatment of step (d) is performed at a temperature of 850°C or higher and 1230°C or lower. Claim 8 A manufacturing method according to claim 1, wherein the heat treatment of step (e) is performed for 1 minute or more and 100 minutes or less. Claim 9 A manufacturing method according to claim 1, wherein the rapid cooling of steps (b) to (e) is performed at a cooling rate of 10 K / sec or more. Claim 10 A characteristic recovery alloy comprising a BCT-FCC microstructure capable of metastable reversible phase transformation, manufactured by the method according to claim 1. Claim 11 A characteristic recovery alloy according to claim 10, having a yield strength of 700 MPa or more. Claim 12 A characteristic recovery alloy according to claim 10, having an ultimate tensile strength of 950 MPa or more. Claim 13 A characteristic recovery alloy according to claim 10, having a maximum elongation of 10% or more. Claim 14 In claim 10, the yield strength of the characteristic return alloy that has undergone one or more strain-return cycles exhibits a difference of 10% or less compared to the yield strength of the characteristic return alloy immediately after manufacturing, and the strain-return cycle comprises deforming the alloy by a tensile strain of up to 90% of the UTS strain, then heat-treating the deformed alloy at 850°C or higher and 1200°C or lower for 30 seconds or more and 30 minutes or less, followed by rapid cooling, and a minimum temperature (T) according to the Mn composition of the cooled alloy. 1,min (℃) = -18 × wt%(Mn) + 640) or higher, maximum temperature (T 1,max A characteristic recovery alloy in which heat treatment at a temperature of (°C) = -18 × wt%(Mn) + 820) or lower for 1 minute or more and 100 minutes or less constitutes one cycle. Claim 15 A method for restoring the properties of a property-restoring alloy that has undergone deformation due to use, manufactured by the method according to claim 1, comprising sequentially performing the following steps: (A) a property-restoring alloy that has undergone deformation due to use, wherein the alloy is subjected to a minimum temperature (T) according to the Mn composition of the alloy. 2,min (℃) = -18 × wt%(Mn) + 820) or higher, maximum temperature (T 2,max (℃) = 0.8 × T m A step of heat treating below ) and then rapidly cooling; and (B) a minimum temperature (T) according to the Mn composition of the alloy 1,min (℃) = -18 × wt%(Mn) + 640) or higher, maximum temperature (T 1,max A step of heat-treating the alloy at (℃) = -18 × wt%(Mn) + 820) or less, followed by rapid cooling. Claim 16 A method according to claim 15, wherein the heat treatment of step (A) is performed for 30 seconds or more and 30 minutes or less. Claim 17 A method according to claim 15, wherein the heat treatment of step (B) is performed for 1 minute or more and 100 minutes or less.
